Cardiac-targeted AAV5-S100A1 gene therapy protects against adverse remodeling and contractile dysfunction in postischemic hearts - Kehr, Dorothea; Salatzki, Janek; Seger, Birgit; Varadi, Karl; Birkenstock, Jennifer; Schlegel, Philipp; Gao, Erhe; Koch, Walter J.; Katus, Hugo; Frey, Norbert; Riffel, Johannes; André, Florian; et al. (Circulation. Heart failure, 2025)
BACKGROUND: - Guided by long-term safety data for AAV5 (adeno-associated virus 5) in humans, our translational study investigated whether AAV5 effectively delivers genes to healthy and achieves therapeutic efficacy in dysfunctional human-sized hearts, using a clinically applicable mode of administration and vector dosages. - METHODS: - AAV-mediated cardiac gene transfer in pigs was performed by percutaneous catheter-based retrograde intravenous vector delivery, and vector genome and transgene expression levels determined by reverse transcription-polymerase chain reaction and immunoblotting. Postmyocardial infarction (MI) cardiac dysfunction porcine and murine models were generated by coronary catheter-based occlusion and ligation, respectively. The study end points left ventricular ejection fraction and left ventricular MI size, were measured by cardiac magnetic resonance imaging and echocardiography. Bulk myocardial RNA-sequencing and weighted gene correlation network analysis were used to link study end points to molecular pathway mechanisms. Safety was assessed by clinical chemistry, blood count and ECG. - RESULTS: - In a first biodistribution study, AAV5 (1×1013 vector genomes; vgs) with the reporter gene luciferase (luc) achieved broad and homogenous transduction of healthy pig hearts 30 days after catheter-based retrograde intravenous vector delivery without toxicity. Both its myocardial and extra-cardiac distribution patterns were advantageous compared with AAV9-luc and AAV6-luc. Using AAV5 with the cardioprotective human gene S100A1 (hS100A1; 1×1013 vgcs) by catheter-based retrograde intravenous vector delivery in a subsequent therapy study in post-MI pigs prevented left ventricular MI extension and improved left ventricular ejection fraction after 3 months without clinical toxicity. Weighted gene correlation network analysis linked novel antiinflammatory actions and cardioprotective signaling mechanisms by hS100A1 to study end point improvements, which was confirmed in a post-MI mouse model. - CONCLUSIONS: - Providing the clinically relevant proof of concept for AAV5 to effectively transduce healthy and dysfunctional human-sized hearts, its clinical long-term safety, scalable producibility, and low preexisting immunity in humans may predestine AAV5 as an effective and safe gene carrier for a prevalent disease such as chronic heart failure, using therapeutic genetic effectors such as hS100A1 or others.
Gesehen am 15.12.2025